Biological monitoring of the environment : manual of methods - Salánki, János; Jeffrey, D; Hughes, G. M (C.A.B. International, 1994)
Biological monitoring of the environment uses living systems and living processes to predict, detect and quantify the harmful effects of water, soil and air pollution. This manual provides a collection of methods tested under various conditions as being suitable for practical use in monitoring environmental pollutants or pollution. Papers have been written mostly by members of the IUBS Interdisciplinary Commission on Bioindicators and fall into six categories: microbiology, cell biology, botany, zoology, comparative biochemistry/physiology and hydrobiology. The organisms assessed include bacteria, fungi, algae, fish, insects and several other invertebrate groups, in aerial, terrestrial and aquatic ecosystems. Some papers provide relevant theoretical background while others are very practical in focus. Methods for use in both field studies and/or laboratory testing are included. Overall the manual should be of interest ot a wide range of students and workers in biological and environmental sciences.
Keywords: biologie; environmentální vědy